Bioinspired Materials: Hyaluronic Acid Catechol: A Biopolymer Exhibiting a pH‐Dependent Adhesive or Cohesive Property for Human Neural Stem Cell Engineering (Adv. Funct. Mater. 14/2013). (4th April 2013) - Hong, Seonki; Yang, Kisuk; Kang, Bobae; Lee, Changhyun; Song, In Taek; Byun, Eunkyoung; Park, Kook In; Cho, Seung‐Woo; Lee, Haeshin
<x xml:space="preserve">Abstract</x> A mussel, which is a sticky organism underwater, provides researchers inspiration to develop novel bio‐adhesives. Catechol is a key chemical moiety for developing such adhesives. The results reported by Seung‐Woo Cho, Haeshin Lee, and co‐workers on page 1774 show the dual roles of catechol, with its properties of cohesion and adhesion depending on environmental conditions such as pH. Catechol is chemically tethered onto hyaluronic acid and the resulting conjugate is demonstrated to be useful for human neural stem cell culture. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>